Surgical Outcomes Of Pars Plana Vitrectomy In Aded And Prognostic Factors For Poor Visual Outcomes - Haseeb, Uzma; Haseeb, Muhammad; Hadi, Abdul; Haseeb, Sahar; Mahmood , Tauseef (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the visual and anatomical outcomes of pars plana vitrectomy (PPV) in patients with advanced diabetic eye disease (ADED) and to determine the prognostic factors associated with poor visual outcomes. Methods: A cross-sectional study was conducted among those who underwent PPV for ADED at Al Ibrahim Eye Hospital from January 2023 to December 2023. Visual acuity before surgery, intraoperative surgical details, and complications after surgery were documented. Outcomes after surgery, including best-corrected visual acuity (BCVA) and retina status, were assessed at 3- and 6-month follow-ups. Indications for surgery included tractional retinal detachment (TRD), persistent vitreous haemorrhage (VH), and vitreomacular interface abnormalities. Bivariate and multivariate logistic regression analyses assessed factors associated with poor visual outcomes. Results: Of the 50 eyes analysed, 67.5% of patients achieved mild vision impairment (6/36 or better) by the final follow-up. Mean BCVA improved significantly from 1.85 logMAR preoperatively to 1.47 logMAR at six months (p < 0.05). Poor preoperative visual acuity, macular involvement, and iris neovascularisation were identified as significant predictors of poor visual outcomes (p < 0.05). Final anatomical attachment was achieved in 82.5% of cases. Postoperative complications included VH (10%), retinal detachment (5%), and neovascular glaucoma (2.5%). Conclusions: To improve or stabilise vision in patients with ADED, PPV proved to be effective with high rates of retinal reattachment. Prognostic factors such as preoperative VA and involvement of the macula emphasise the need for timely intervention and careful intraoperative management to optimise outcomes. Keywords: Retinal detachment, Vitrectomy, Visual acuity, Diabetic retinopathy.